Analysis of Destination Marketing Management in Papandayan Nature Tourism Park, Garut, West Java - Roels Ni Made Sri Puspadewi; Budi Setiawan; Nisa Rahmaniyah Utami (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2024)
As a tourist destination, various types of marketing strategies are needed in order to ensure the sustainability of the Papandayan Nature Tourism Park and maintain the natural beauty of Mount Papandayan so that it can continue to be enjoyed for a long time. This study uses Qualitative data analysis techniques using secondary data collection techniques. Data collection techniques used include Literature Review and Observation at the Papandayan Nature Tourism Park. The purpose of this study is to determine the implementation and influence of Destination Marketing Management in the Papandayan Nature Tourism Park. The results of this study are that the Papandayan Nature Tourism Park has so far implemented many marketing strategies which are marked by an increase in visitors each year, adequate infrastructure, various types of attractions provided and good responses from visitors. The suggestion that can be given from this study is that in the future it would be better if the Papandayan Nature Tourism Park could promote itself more, especially using various platforms such as Websites or Social Media to introduce the Tourist Destination to a wider audience. This is because currently the information available in the media is still relatively minimal and it is still difficult to find out the exact information contained in Papandayan unless tourists visit the place first or see the reviews left by previous visitors.